Ms. Sue has no clue! - Gutman, Dan; Paillot, Jim (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2013)
"Alexia's mom, Ms. Sue, leads the kids of Ella Mentry School in the weirdest fundraiser in the history of the world!"--
Accelerated Reader AR
Keywords: Fund raising -- Juvenile fiction; Carnivals -- Juvenile fiction; Schools -- Juvenile fiction; Humorous stories